2022
DOI: 10.3390/v14091900
|View full text |Cite
|
Sign up to set email alerts
|

Are Viral Infections Key Inducers of Autoimmune Diseases? Focus on Epstein–Barr Virus

Abstract: It is generally accepted that certain viral infections can trigger the development of autoimmune diseases. However, the exact mechanisms by which these viruses induce autoimmunity are still not understood. In this review, we first describe hypothetical mechanisms by which viruses induce some representative autoimmune diseases. Then, we focus on Epstein–Barr virus (EBV) and discuss its role in the pathogenesis of rheumatoid arthritis (RA). The discussion is mainly based on our own previous findings that (A) EBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
0
11
0
1
Order By: Relevance
“…51 In addition, autoimmune diseases linked to EBV include systemic lupus erythematosus, 52 multiple sclerosis, 53 or rheumatoid arthritis. 54 It is suggested that EBV may contribute to the onset or exacerbation of autoimmune disorders. Despite these insights, the precise role of such RNAs in autoimmune diseases remains unclear, warranting further investigation of the complex interplay between the virus and the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…51 In addition, autoimmune diseases linked to EBV include systemic lupus erythematosus, 52 multiple sclerosis, 53 or rheumatoid arthritis. 54 It is suggested that EBV may contribute to the onset or exacerbation of autoimmune disorders. Despite these insights, the precise role of such RNAs in autoimmune diseases remains unclear, warranting further investigation of the complex interplay between the virus and the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the convincing data about the role of EBV in MS, EBV has long been associated with other autoimmune diseases (AI), specifically systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and Sjögren syndrome (SS) [ 151 ]. As in MS, a higher prevalence of EBV infection, higher titers in serum anti-EBV antibodies, and a higher viral load in blood were reported in SLE, RA, and SS, sometimes correlated with disease activity.…”
Section: Immune-mediated Inflammatory Diseases (Imids)mentioning
confidence: 99%
“…Virale Arthritis [61] Parasitosen: Plasmodien, Filarien, Helmitoden, Lamblien Arthralgien, Arthritiden [62] erhöhtes Risiko einer infektiösen Arthritis assoziiert mit: * HLA-B27, # Sichelzellanämie…”
Section: Tripperarthritisunclassified